The Blurring of Boundaries between Research and Everyday Life: Dilemmas of Employing One’s Own Experiential Knowledge in Disability Research - Mogendorff, Karen (Disability Studies Quarterly, 2013)
Researchers with experiential disability knowledge increasingly engage in socio-medical research. In this paper the author discusses her experiences with employing her own lived experiences with disability in academic and non-academic research projects. Incorporating one’s own lived experiences in research implies a blurring of boundaries between the private, the professional, and the public. The latter may give rise to dilemmas of double membership and dilemmas of disclosure in publications. Double membership may become problematic for disabled researchers who identify with the disability community if conceptualizations of disability in scientific communities unwittingly echo negative societal images of disability. Because of the low status of disabled people and of experiential knowledge, disclosure of own experiences with disability may negatively influence young disabled researchers’ careers. Key Words: deployment of experiential knowledge, the researcher in disability studies, dilemmas